New technique to isolate Cercospora coffeicola Berkeley & Cooke, etiologic agent of cercospora leaf spot of coffee tree - Santos, Leandro Alvarenga; Souza, Paulo Estevão de; Pozza, Edson Ampélio; Caldeira, Douglas Massimo; Botelho, Deila Magna dos Santos (Coffee Science - ISSN 1984-3909, 2014)
The stain brown eye is an endemic disease in Brazil. There are few published studies on this disease because of the difficulty of isolation and production of the fungus Cercospora coffeicola. This work aims to publicize this isolation technique developed and used in UFLA called Pipette Technique. Through this already over 70 isolates were obtained for future studies of the etiologic agent of this important disease.